PUPUK KANDANG SAPI DAN PUPUK ABG BERPENGARUH TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata Sturt) - Dartius ,; Asritanarni Munar; Muhammad Taufik (AGRIUM: Jurnal Ilmu Pertanian, 2012)
AbstractThis study aims to determine the growth and production of sweet corn on the provision of cow manure and ABG fertilizer. The design used was Randomized Design Group factorial with two factors were studied, namely: Cow Manure factor (K) is divided into 4 level without giving Ko =, K1 = 2 kg / plot, K2 = 4 kg / plot, and K3 = 6 kg / plot, and the factor ABG fertilizer (A) divided into 4 standard, namely A0 = no treatment (control), A1 = 2 cc / l of water, A2 = 4 cc / l of water, and A3 = 6 cc / l of water. Cow manure as the first factor and ABG fertilizer as second factor, while the parameters measured were plant height (cm), age of flowering (days), cob length (cm), cob weight (kg), dry seed weight (g), number of leaves (pieces) and leaf area (cm2). The results showed that administration of cow manure (K) gives a marked influence on all parameters except number of leaves observed. ABG fertilizer (A) gives significant effect on leaf area, cob length and cob weight and height parameters are not significant at the plant, leaf number and age of flowering. While the interaction treatment gives a significant influence on the length parameter cob and leaf area, and no real effect on plant height, leaf number, flowering age, weight and cob weight of dry beans.Keywords: cow manure, fertilizer, growth, production, Zea mays saccharata Sturt